Factors influencing productivity in sympatric populations of Mountain reedbuck and Grey rhebok in the Sterkfontein Dam Nature Reserve, South Africa - Krecek, R.C. (University of Pretoria, 2013)
Thesis (PhD (Veterinary Wildlife))--University of Pretoria, 2004.